Instability of stratified two-phase flows in rectangular ducts. (October 2020) - Gelfgat, Alexander; Brauner, Neima
Highlights: Stability of stratified two-phase pressure driven flow in rectangular pipes is studied. The results are obtained via solution of the eigenproblem associated with the linear stability of the flow. All possible three-dimensional infinitesimal disturbances are considered. Two cases of liquid-liquid and air-water systems are studied. The results are presented as stability diagrams and patterns of the most unstable perturbations. Abstract: The linear stability of stratified two-phase flows in rectangular ducts is studied numerically. The linear stability analysis takes into account all possible infinitesimal three-dimensional disturbances and is carried out by solution of the associated eigenproblem. The neutral stability boundary and the corresponding critical wave number are obtained for liquid – liquid and air – water systems. Depending on the problem parameters, the instability sets in owing to short, intermediate, or long wave most unstable perturbations. Patterns of the most unstable disturbances are reported and discussed. It is shown that the instability arises due to shear, or interfacial mechanisms. Effects of the surface tension and of width/height aspect ratio are also studied. The results support the premise that the stability analysis of stratified two-phase flow in the simpler geometry of two-infinite plates can provide a reasonable estimation of the conditions for which this flow pattern can be considered to be linearly stable.